2018
DOI: 10.1590/0034-7167-2017-0121
|View full text |Cite
|
Sign up to set email alerts
|

Calf circumference: clinical validation for evaluation of muscle mass in the elderly

Abstract: Objective: To validate calf circumference as a technology for assessing muscle mass in the elderly. Method: Cross-sectional study with 132 elderly people from Goiânia, Goiás, Brazil. Decreased muscle mass was determined by the skeletal muscle mass index (IME) using Dual Energy X-Ray Absortometry (DEXA). The cutoff circumferences (CC) cutoff points to indicate muscle mass decrease were estimated by ROC curve, sensitivity, specifi city and accuracy. Results: The most accurate cut-off points for detecting decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1
41

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 36 publications
7
69
1
41
Order By: Relevance
“…7,8,11 Although it should be noted that different ASM/height 2 cut-offs were employed for determining LMM, four studies conducted in Brazil, France and South Africa revealed optimal calf circumference cut-offs of 34 cm (sensitivity 61-71%, specificity 76-77%) for men and 30-33 cm (sensitivity 80-100%, specificity 76-93%) for women, similar to those reported in studies that examined Asian individuals, except for one study where calf circumference was measured in the supine position. 9,10,26,27 The results of our study and those of previous studies suggest that maximum calf circumference is a simple and accurate surrogate marker for finding cases of LMM as assessed by BIA or DXA. However, criteria should be established for optimal cut-offs that account for measurement conditions, such as posture and edema, given that few studies examined optimal calf circumference cutoffs, and measurement conditions such as posture can vary.…”
Section: Discussionsupporting
confidence: 71%
“…7,8,11 Although it should be noted that different ASM/height 2 cut-offs were employed for determining LMM, four studies conducted in Brazil, France and South Africa revealed optimal calf circumference cut-offs of 34 cm (sensitivity 61-71%, specificity 76-77%) for men and 30-33 cm (sensitivity 80-100%, specificity 76-93%) for women, similar to those reported in studies that examined Asian individuals, except for one study where calf circumference was measured in the supine position. 9,10,26,27 The results of our study and those of previous studies suggest that maximum calf circumference is a simple and accurate surrogate marker for finding cases of LMM as assessed by BIA or DXA. However, criteria should be established for optimal cut-offs that account for measurement conditions, such as posture and edema, given that few studies examined optimal calf circumference cutoffs, and measurement conditions such as posture can vary.…”
Section: Discussionsupporting
confidence: 71%
“…It is known that elderly individuals with lower CC have a greater deficiency and less physical function [ 19 ], besides being a measurer to identify the decrease of muscle mass in the elderly [ 29 ]. However, in our study, the NC was the one that best correlated with SMM.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, 43.7% of patients had, at the time of admission, the calf circumference below the cohort point. In last years, there was an increase in publications with calf circumference to in different populations for different outcomes, mainly because it is a good marker of muscle mass in older patients 31 , has an association with sarcopenia 32 , is a predictor of readmission 33 and mortality. 34 Because it is an easy-to-measure and low-cost measure, it can be part of the routine assessment of hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%